Assessment of surface crack growth of composite girders with concrete-filled tubular flanges and corrugated webs through substructure-based numerical modelling. (1st February 2022) - Wang, Z.Y.; Shi, Y.Z.; Zhou, X.F.; Shao, Y.B.
Graphical abstract: Highlights: Substructure-based model is developed for corrugated web-tube welded details. Stress gradient and geometry effects are corrected for structural stress intensity factors. Predicted crack growth increment allowing coupled effects agrees well with test result. Abstract: This paper presents an analytical assessment of surface crack growth behaviour of composite girders with concrete filled tubular flanges and corrugated webs (CGCTFCWs) with the aid of substructure-based numerical modelling. Distinctive features of crack propagation on the tubular flanges with considerable stress gradient from lower to upper cracked tube surface interacted with the weld toes along the corrugated webs are replicated in the substructure modelling and discussed in details. Based on a favourable verification of stress intensity factors (SIFs) with reported model with semi-elliptical surface crack in plates and rectangular hollow section tube, an analytically derived substructure model of critical corrugated web-flange welded details coupled to the rest of the structure is developed. Such a model is distinguished itself from that based on original Newman and Raju equation by an amendatory of the stress gradient induced by the shifting of the neutral axis and the geometry as crack penetrated through the tube wall. Based on a parametric analysis, the SIFs significantly influenced by the corrugation depth ratio, the tube thickness-to-width ratio and the tube thickness-to-depth ratio in relation with the dimensionless crack length are demonstrated and taken into account in the derivation of a new geometry amendatory coefficient. An experimental investigation was also implemented to further examine and validate the modelling crack propagation response. The resultant fatigue fracture manner and the stress concentration of the hot spot are virtually in good correlation with the modelling results. Moreover, the relations between the crack growth increment and fatigue endurances from experimental measurement match well with these predicted by the NASGRO equation using amended SIFs, indicating that the proposed model is able to trace the distinct geometry effects of the corrugated web and the tubular flange on the crack propagation response of CGCTFCWs.